Connecting Human Resource Practices Employer Branding Employee Engagement And Talent Retention: Menghubungkan Praktik Sumber Daya Manusia Employer Branding Keterikatan Karyawan Dan Retensi Talenta - Nova Devina Veronika; Werner R. Murhadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Retaining quality personnel has become a strategic necessity for organizations navigating dynamic business competition. Specific Background PT Bumi Hutani Lestari, an oil palm company in Central Kalimantan, faces challenges in preserving high-quality workers due to high labor mobility within the industry. Knowledge Gap Previous research has independently explored variables like organizational reputation along with worker commitment, yet an integrated framework uniting these elements within a single comprehensive model remains absent, particularly within the Indonesian corporate context. Aims This study investigates the interrelationships among workforce administration strategies, corporate identity, worker participation, along with personnel stability using a quantitative survey of 297 individuals analyzed via Structural Equation Modeling. Results The analysis reveals that structured personnel administration positively shapes both corporate identity alongside worker participation. Furthermore, corporate identity positively determines worker participation coupled with personnel stability, while worker participation significantly sustains personnel stability. Novelty This research successfully synthesizes previously fragmented variables into a unified structural model, validating the sequential mediation of organizational reputation alongside worker participation within the highly competitive palm oil sector. Implications Organizations must strategically prioritize integrated personnel policies, specifically transparent recruitment alongside competitive compensation, to cultivate a robust corporate identity, thereby securing long-term personnel stability. Highlights Comprehensive workforce policies positively shape organizational reputation alongside personnel commitment. A robust corporate identity significantly secures long-term worker loyalty coupled with active participation. Active participation serves as a critical mechanism linking corporate reputation with personnel stability. Keywords Human Resource Practices; Employer Branding; Employee Engagement; Talent Retention; Structural Equation Modeling